Pemanfaatan Biogas Dari Sisa Makanan Sebagai Langkah Pengurangan Food Waste & Food Loss - Agustin, Laila; Deswita, Rania; S, Selpia (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Food waste and food loss are global problems that affect environmental sustainability and food safety. There are many ways to overcome this, one of which is by using biogas. Biogas is an energy source produced from the process of decomposing organic materials by microorganisms. In this context, food waste can be an ideal raw material for biogas production through a degradation process, the biogas produced consists of methane and carbon dioxide gas. This research aims to determine the potential of biogas produced from food waste and food loss. The approach used in this research uses a quantitative approach, with experimental methods in data collection. This biogas production experiment involves a degradation process, where the material used is stored in a closed medium to speed up the biogas production process. Utilizing biogas can be an effective step in reducing the amount of organic waste entering landfills, and can be used as an alternative fuel for the community. This research shows that there is methane gas produced from biogas made from food loss and food waste, so that when testing the flame, a fire response is produced.